Mutant ts1 of bacteriophage PM2 is defective in the major capsid protein and fails to package its DNA. - Brewer, G J (1983)
Infection of Alteromonas espejiana at restrictive temperature with mutant ts1 of bacteriophage PM2 resulted in the intracellular accumulation of virus-sized empty-appearing membrane vesicles. The DNA associated with purified vesicles was fully susceptible to digestion with DNase. Sedimentation analysis and electron microscopy suggested a full-length linear form of the normally circular viral genome. A pulse-chase-shift experiment suggested that [3H]thymidine-labeled DNA made under restrictive conditions is assembled into virions after shift to permissive temperature. A defective structural protein in the ts1 virion appears to be the cause of a rapid rate of thermal inactivation of infectivity. Analysis of the proteins of ts1 by isoelectric focusing indicated a more alkaline isoelectric mobility of the major capsid protein, sp27. Six spontaneous revertants of ts1 showed reversion to the wild-type isoelectric form of sp27. These results identify sp27 as the defective gene product of ts1. Taken together, these results suggest that the membrane of PM2 is formed without the aid of an inner core or an outer scaffolding.